Strength-Based Counseling: Alternative Counseling to Increase Student Hope during the COVID-19 Pandemic - Asiah, Nur; Rusmana, Nandang; Saripah, Ipah (Department of Guidance and Counseling, FIP, Undiksha, 2022)
COVID-19 has affected the world of education in particular. The COVID-19 pandemic created a new conceptualization of schools with learning methods changed to learning from home, having limited interaction with teachers and classmates. Transitioning and adapting to a new way of life has an emotional impact on students. The current situation creates uncertainty, fear, and hopelessness. The emergence of despair in students is an example of the low power of hope in students, which will have a broad impact on other dimensions of life. This study is a literature review that discusses how strength-based counseling can help increase student hope during COVID-19. This literature review can be used as a reference for counselors through the self-strength counseling model.